Management and modelling of the industrial enterprise's crisis situations - Rayevnyeva, Olena; Brovko, Olha; Filip, Stanislav; Aksonova, Iryna; Derykhovska, Viktoriia (LLC "СPС "Business Perspectives", 2020)
In conditions of national economy’s unstable development, the primary task of the enterprise internal management is to timely assess and predict the effects of external fluctuations on the state of the enterprise and to develop effective management decisions. The article aims to develop the methodological approach, which, based on a set of models for recognizing an artificial crisis or localizing a natural crisis, allows the crisis management of an enterprise considering its resource capabilities and stage of the life cycle as the interaction of system-forming spheres of life, namely production, financial, and labor. The practical value of the approach consists in developing a system of econometric and cognitive modeling models that allows developing a set of managerial decisions that are adaptive to external and internal fluctuations for localizing a natural crisis or recognizing an artificial crisis. The methodological approach was implemented at Ukrainian industrial enterprises. As the results of the study, several different scenarios of solutions for crisis management of the enterprise were obtained.
Keywords: methodological approach; enterprises; sphere of activity; cycle of development; point of crisis; cognitive model; impulse; management decision